Triadic interaction among young children and their mothers and fathers - Brewster, Lynne C. (1998)
Recent research into the interaction which occurs between mother, father and child has tended to view the interaction as two dyadic interactions, one occurring between the mother and the child and the other occurring between the father and the child (Barton and Tomesello, 1994). None of these studies have viewed the triadic interaction which exists when mother, father and child are present as anything other than a series of dyadic interactions.